(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
I show, in this original research paper, that the famous Riemann Hypothesis is true by proving that its simple Balazard equivalent form (cited, without proof, in [1] p 16 as the equivalent form 5), which I prove here using [22] and [30], is true. The proof is essentially based on elementary tools of mathematics; it uses the topological properties of the functions: